The Ultimate Display for Physical Rehabilitation: A Bridging Review on Immersive Virtual Reality - Elor, Aviv; Kurniawan, Sri (Frontiers in Virtual Reality, 2020)
Physical rehabilitation is often an intensive process that presents many challenges, including a lack of engagement, accessibility, and personalization. Immersive media systems enhanced with physical and emotional intelligence can address these challenges. This review paper links immersive virtual reality with the concepts of therapy, human behavior, and biofeedback to provide a high-level overview of health applications with a particular emphasis on physical rehabilitation. We examine each of these crucial areas by reviewing some of the most influential published case studies and theories while also considering their limitations. Lastly, we bridge our review by proposing a theoretical framework for future systems that utilizes various synergies between each of these fields.